2015
DOI: 10.1038/srep11569
|View full text |Cite
|
Sign up to set email alerts
|

The effect of land-use on the diversity and mass-abundance relationships of understory avian insectivores in Sri Lanka and southern India

Abstract: Understory avian insectivores are especially sensitive to deforestation, although regional differences in how these species respond to human disturbance may be linked to varying land-use histories. South Asia experienced widespread conversion of forest to agriculture in the nineteenth century, providing a comparison to tropical areas deforested more recently. In Sri Lanka and the Western Ghats of India, we compared understory insectivores to other guilds, and to insectivores with different vertical strata pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Nevertheless, marked changes in avian community structure following logging suggest that other ecosystem properties in logged forests may be different from that of primary forests, representing an important topic for future studies. These different responses found between Srinivasan () and Sreekar et al () may be due to the degree of habitat variation. For instance, Srinivasan () sampled across a gradient of selective logging intensities, while this study and Sreekar et al () sampled across a gradient of distinct habitats which are more drastically different from each other.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Nevertheless, marked changes in avian community structure following logging suggest that other ecosystem properties in logged forests may be different from that of primary forests, representing an important topic for future studies. These different responses found between Srinivasan () and Sreekar et al () may be due to the degree of habitat variation. For instance, Srinivasan () sampled across a gradient of selective logging intensities, while this study and Sreekar et al () sampled across a gradient of distinct habitats which are more drastically different from each other.…”
Section: Discussionmentioning
confidence: 79%
“…Sreekar et al () also found no difference in the mass–abundance relationship of avian communities between primary forests and selectively logged forests in southern India. Sreekar et al () suggested that this similarity was due to high species turnover in logged forests, as the avian communities change in response to altered environments.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations